Exploring university-to-college transfer in Ontario: A qualitative study of non-linear post-secondary mobility - Maier, Reana; Robson, Karen (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
In this study, we explored the experiences of Ontario students who have engaged in a ‘reverse transfer’, i.e. moving from university-to-college (UTC). Data was collected through qualitative interviews with 20 participants who began their post-secondary journey in a university program, but left that program before completing it, and subsequently pursued a college program. We focused on the factors that led to the decision to reverse transfer, participants’ experiences and perceptions of the reverse transfer process, and what, if any, barriers they experienced. We found that motivations for leaving university were distinct from, though sometimes related to, motivations for pursuing college. Reasons for leaving university were clustered around three themes: academic struggles, mental/physical health/special education need struggles, and future prospects. These were highly interconnected and characterized by difficulties, ranging from mild to severe, coping with university. Motivations for pursuing college were more practical and straightforward, relating to subject interest, college learning environment, location, and future prospects. While most participants reflected very positively on their decision to transfer, there were some negative or ambivalent reflections about having left university before completing their degrees. These were largely related to a sense of personal failure and/or the negative reactions of others, particularly parents. Personal and external (usually parental) negative reflections were tied to cultural and societal expectations about high achievement and perceptions of university education as superior to college education. We conclude with policy recommendations.